Assessment of the Relationship Between Sarcopenia and Body Composition, Nutrition, Physical Performance, and Functional Status in Older Adults - Yahya Doğan; Pınar Borman; Pelin Bilgiç; Sümeyra Öteleş; Nagihan Kırcalı Haznedar; Sevilay Karahan; Yeşim Gökçe Kutsal (Türk Osteoporoz Dergisi, 2025)
Objective: The aim of this study was to evaluate the presence of sarcopenia in elderly patients and to examine its relationship with body composition, nutritional status, muscle strength and physical performance. Materials and Methods: In this cross sectional study, patients aged 60 and older who attended the physical medicine and rehabilitation outpatient clinic of a university hospital between June 2018 and June 2019 were enrolled. Demographic and anthropometric data were collected. Sarcopenia was screened using the SARC F questionnaire (score ≥4), while muscle mass was evaluated by bioelectrical impedance analysis. Functional parameters were assessed using hand grip strength, a 4 meter gait speed test, the chair sit to stand test (CSST), balance tests, and the short physical performance battery. Nutritional status was evaluated using the full mini nutritional assessment, and physical activity was measured using the Turkish version of the physical activity scale for the elderly. Results: The overall prevalence of sarcopenia was 41.0%, with no significant gender differences. SARC F scores were significantly associated with several physical performance measures, notably balance and chair stand test performance. Logistic regression analysis demonstrated that better balance and CSST performance were inversely associated with high SARC F scores, while a higher body mass index increased the likelihood of a high SARC F score. Conclusion: Although the SARC F questionnaire effectively identifies key characteristics of sarcopenia and correlates with certain functional measures, its utility as a standalone diagnostic tool remains limited. Comprehensive assessment including muscle mass and strength evaluations is recommended for a definitive diagnosis.